Objective Structured Assessments of Technical Skills (OSATS) Does Not Assess the Quality of the Surgical Result Effectively. Issue 4 (April 2016) - Anderson, Donald D.; Long, Steven; Thomas, Geb W.; Putnam, Matthew D.; Bechtold, Joan E.; Karam, Matthew D.
Abstract: Background: Performance assessment in skills training is ideally based on objective, reliable, and clinically relevant indicators of success. The Objective Structured Assessment of Technical Skill (OSATS) is a reliable and valid tool that has been increasingly used in orthopaedic skills training. It uses a global rating approach to structure expert evaluation of technical skills with the experts working from a list of operative competencies that are each rated on a 5‐point Likert scale anchored by behavioral descriptors. Given the observational nature of its scoring, the OSATS might not effectively assess the quality of surgical results. Questions/purposes: (1) Does OSATS scoring in an intraarticular fracture reduction training exercise correlate with the quality of the reduction? (2) Does OSATS scoring in a cadaveric extraarticular fracture fixation exercise correlate with the mechanical integrity of the fixation? Methods: Orthopaedic residents at the University of Iowa (six postgraduate year [PGY]‐1s) and at the University of Minnesota (seven PGY‐1s and eight PGY‐2s) undertook a skills training exercise that involved reducing a simulated intraarticular fracture under fluoroscopic guidance. Iowa residents participated three times during 1 month, and Minnesota residents participated twice with 1 month between their two sessions. A fellowship‐trained orthopaedic traumatologist rated each performance using a modified OSATS scoring scheme. The quality of the articular reduction obtained was then directly measured. Regression analysis was performed between OSATS scores and two metrics of articular reduction quality: articular surface deviation and estimated contact stress. Another skills training exercise involved fixing a simulated distal radius fracture in a cadaveric specimen. Thirty residents, distributed across four PGY classes (PGY‐2 and PGY‐3, n = 8 each; PGY‐4 and PGY‐5, n = 7 each), simultaneously completed the exercise at individual stations. One of three faculty hand surgeons independently scored each performance using a validated OSATS scoring system. The mechanical integrity of each fixation construct was then assessed in a materials testing machine. Regression analysis was performed between OSATS scores and two metrics of fixation integrity: stiffness and failure load. Results: In the intraarticular fracture model, OSATS scores did not correlate with articular reduction quality (maximum surface deviations: R = 0.17, p = 0.25; maximum contact stress: R = 0.22, p = 0.13). Similarly in the cadaveric extraarticular fracture model, OSATS scores did not correlate with the integrity of the mechanical fixation (stiffness: R = 0.10, p = 0.60; failure load: R = 0.30, p = 0.10). Conclusions: OSATS scoring methods do not effectively assess the quality of the surgical result. Efforts must be made to incorporate assessment metrics that reflect the quality of the surgical result. Clinical Relevance: New objective, reliable, and clinically relevant measures of the quality of the surgical result obtained by a trainee are urgently needed. For intraarticular fracture reduction and extraarticular fracture fixation, direct physical measurement of reduction quality and of mechanical integrity of fixation, respectively, meet this need.